THEORETICAL ANALYSIS OF THE PEDAGOGICAL CONDITIONS FOR THE FORMATION OF RESEARCH SKILLS IN STUDENTS BY WORKING ON PROBLEMS RELATED TO THE ASSESSMENT OF PHYSICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It is known that the concept of education is changing in the secondary education system of our republic based on international experiences. In other words, according to the previous concept, imparting knowledge to students is the main thing, but now, together with imparting knowledge, learning to acquire knowledge and collect information, forming skills of data processing and their practical application form the concept of modern education.